Neue Slowenische Kunst in misel kot središče avantgardnosti - Mršek Bajda, Lela Angela (Amfiteater (Ljubljana), 2025)
The comprehension of centre and periphery in culture is subject to historical changes. In this process, instead of being monolithically paradigmatised, this comprehension itself also becomes a complex of multiplied multifacetedness. The paper develops this thesis by observing the events between the performativity of Neue Slowenische Kunst (NSK) and Ljubljana’s urban subculture around 1980 and between the performativity of Neue Slowenische Kunst and the para-civic movement NSK Folk Art around 2010. Performative appropriations unfolded among these practices, which led to the subversion of the central and peripheral within the cultural counter-current to the social hegemony. The latter is the result of the ability or inability to build a habitus, that is, a web of memory and understanding of history, expressible within the linguistic grammar of a (sub)cultural group. NSK remains an aesthetic impulse that empowers socially engaged thought but loses its position as the absolute centre of this thought because it distances itself from its embodiment, thereby – paradoxically – intensifying the existential dimensions of its own performativity. The border between the cultural centre and the cultural periphery becomes blurred, thus making the avant-garde attack on culturally expressed hegemonies problematic.
Keywords: avantgarda; avant-garde; centre; habitus; Neue Slowenische Kunst; obrobje; periphery; središče; subculture; subkultura